2020
DOI: 10.3390/vaccines8020284
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4 Blockade, during HIV Virus-Like Particles Immunization, Alters HIV-Specific B-Cell Responses

Abstract: Studies have shown that blockade of CTLA-4 promoted the expansion of germinal center B-cells in viral infection or immunization with model antigens. Few studies have evaluated the immunological consequences of CTLA-4 blockade during immunization against relevant vaccine candidates. Here, we investigated the effects of CTLA-4 blockade on HIV virus-like particles (VLPs) vaccination in a C57BL/6J mouse model. We found that CTLA-4 blockade during HIV VLP immunization resulted in increased CD4+ T-cell activation, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 95 publications
(175 reference statements)
0
9
1
Order By: Relevance
“…CTLA-4 blockade in ART-treated RMs increased T-cell activation and viremia, but did not augment responses to vaccination, nor increase SIV-specific responses [601]. This is contrary to a mouse study which demonstrated increased HIV-specific B-cell and T follicular helper responses with CTLA-4 blockade combined with HIV virus-like particle vaccination [602]. Thus, the evidence points towards a potential usage for CTLA-4 blockade as an immune boosting agent when combined with an LRA, as standalone CTLA-4 blockade does not potently reactivate virus.…”
Section: T-cell Exhaustion and Targeted Therapiescontrasting
confidence: 75%
“…CTLA-4 blockade in ART-treated RMs increased T-cell activation and viremia, but did not augment responses to vaccination, nor increase SIV-specific responses [601]. This is contrary to a mouse study which demonstrated increased HIV-specific B-cell and T follicular helper responses with CTLA-4 blockade combined with HIV virus-like particle vaccination [602]. Thus, the evidence points towards a potential usage for CTLA-4 blockade as an immune boosting agent when combined with an LRA, as standalone CTLA-4 blockade does not potently reactivate virus.…”
Section: T-cell Exhaustion and Targeted Therapiescontrasting
confidence: 75%
“…Both G4-70/30 PAMAM and β-cyclodextrin derivative AMC6 polycationic nanoparticles were able to bind and deliver the antigenic peptide to DCs. We have chosen an antigenic peptide derived from the gag p24 protein since this protein have been shown to be antigenic in several vaccine preparation attempts [ 14 ]. We failed in a previous work to induce a robust antigenic response using as delivery agent a cationic phosphorous dendrimer [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…We explored this approach using a cationic phosphorous dendrimer which failed to induce an efficient antigenic response [ 13 ]. Since gag-derived peptides (including p24-derived peptides) have potential antigenic activity [ 14 ], we decided to explore whether other NPs with different chemical structure were able to deliver the peptide in such a way that it would produce a significant antigenic response. This was the rationale to perform the present experiments since we think that NPs can be very helpful tools to potentiate the antigenic presentation and so contribute to elicit a potent immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a murine study indicated a potential adjuvant role of anti-CTLA-4 as CTLA-4 blockade during HIV immunization in mice led to increased CD4+ T-cell activation, expansion of HIV specific follicular helper T-cell (Tfh) cells, altered HIV specific B-cell responses and significantly increased anti-HIV antibodies with higher avidity and antibody-dependent-cellular cytotoxicity (ADCC) capabilities. 44 …”
Section: Ctla-4mentioning
confidence: 99%
“…In animal models, ICB during vaccination improved protective efficacy 36 and increased levels of anti-HIV antibodies with higher antibody-dependent cellular cytotoxicity capabilities. 44 …”
Section: Outstanding Questionsmentioning
confidence: 99%